Educators’ Perceptions of Performance-Based Approaches in Teaching Difference With Youth (LEARNing Landscapes, 2020)
Recent research into critical pedagogy supports the implementation of performance-based practices into the classroom. This qualitative research explored the pragmatic ways in which youth, ages 8-17, are  taught in Canada’s, specifically Ontario’s, education system on topics of difference and power. Through semi-structured interviews, four elementary and high school educators described their experiences using performance-based teaching in the classroom. A thematic analysis revealed that teachers found including such practices empowered students and influenced their understanding of their own identities as well as the systemic oppression of marginalized groups.
Keywords: oppression; critical pedagogy; social justice; drama education; performative inquiry